MATHEMATICAL MODELING FOR PROCESS OF TUBE POLARIZATION - LUKOVYCH, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
A mathematical model of calculation of parameters of a cathode protection system of a main pipeline during polarization process is built. In the model values of current density, polarization potential and polarization resistance in the part of a pipe surface which has direct contact with electroconductive medium, are calculated. The calculations are done under the condition that the value of this part of known. The dependence between the potential gradient and the current at the metal-electrolyte interface is determined using the data from the polarization curve.